Methanogen Community Dynamics and Methanogenic Function Response to Solid Waste Decomposition - Yang, Shu; Li, Lei; Peng, Xuya; Zhang, Rui; Song, Liyan (Frontiers in Microbiology, 2021)
Methane production during solid waste decomposition is a typical methanogen-mediated and enzyme-catalyzed anaerobic digestion (AD). Methanogen community dynamics and metabolic diversity during the decomposition are not known. In this study, we investigated methanogen community dynamics and methanogenic pathways during solid waste decomposition in a bioreactor using high-throughput Illumina MiSeq sequencing and phylogenetic investigation of communities by reconstruction of unobserved states (PICRUSt), respectively. We also related the methanogen community differences with solid waste and leachate physiochemical parameters. Results showed that the percentage of biodegradable matter (BDM) in solid waste decreased from 55 ± 5% in aerobic phase (AP) to 30 ± 2% in anaerobic acid phase (ACP), and to 13 ± 11% in methanogenic phase (MP), resulting in 76% BDM consumption by microbes. Methanogen community structure varied in AP, ACP, and MP, showing that Methanomicrobiales and Methanosarcinales were dominant in AP and MP and archaea E2 was abundant in ACP. Each phase had abundant core methanogen orders, genera, and species with significant difference (p < 0.05). Redundancy analysis showed that biochemical oxygen demand (BOD5) and nitrate significantly influenced methanogen community composition, suggesting that methanogen community structure is nutrient-dependent. Two methanogenic pathways including acetoclastic and hydrogenotrophic pathways with associated functional genes differed at three phases. ACP had the lowest abundance of these genes, indicating that methanogenesis was inhibited in acidogenesis. Abundant hydrogenotrophic and acetoclastic methanogenesis functional genes in MP and AP are in response to the abundance of Methanomicrobiales and Methanosarcinales. The findings provide previously unidentified insight into the mechanism of methanogen community structure and function during solid waste bioconversion for methane.